Pemenuhan Hak Aksesibilitas Penyandang Disabilitas - Mastari, Tirsa Kiay (Universitas Muhammadiyah Metro, 2025)
Fulfillment of accessibility rights for persons with disabilities is an essential part of efforts to create inclusive and friendly areas for all citizens. Accessibility is not only limited to physical access to the environment, but also includes services and information available to the community. The government and community need to work together to ensure that people with disabilities have a balance of opportunities in accessing the same areas and services as the general public in accordance with applicable norms. Through a normative juridical approach, the analysis focuses on legal norms by using various legal materials. This research examines laws and other legal sources, then analyzes them to understand their content and meaning. In this context, it is important for society and government to ensure the social inclusion and full participation of people with disabilities in various life situations. This study found that the right to accessibility has not been fulfilled, including the provision of environments, services, information and transportation that all individuals can access, including individuals with physical, sensory, intellectual and combination disabilities. Efforts involve the design of universal, integrated infrastructure and technologies and services that are tailored to the needs of each individual. With these steps, equitable and inclusive human rights for people with disabilities can be realized.